Operations research : models and methods - Jensen, Paul A., 1936-; Bard, Jonathan F. (Hoboken, N.J. : [Great Britain] : Wiley, 2003)
This text is designed to bridge the gap between theory and practice by presenting the quantitative tools and models most suited for modern operations research. The principal goal is to give analysts, engineers, and decision makers a larger appreciation of their roles by defining a common terminology and by explaining the interfaces between the underlying methodologies. This text is accompanied by easy-to-use, customized software in the form of Excel add-ins. This software allows the reader to solve a great variety of problems including those presented in the text, homework assignments, and problems that might arise from real-world applications. There are also three commercial software packages provided with the text: an improved version of the optimization engine that comes with Excel, a mathematical programming language that allows the user to enter large, structured problems in algebraic form and a state-of-the-art discrete event simulation package that is widely used by the industry. Suitable for a one-or two-term Senior or first year graduate course in operations research for all engineering majors.
Problem Solving With Operations Research -- linear Programming Models -- Linear Programming Methods -- Sensitivity Analysis, Duality, and Interior Point Methods -- Network Flow Programming Models -- Network Flow Programming Methods -- Integer Programming Models -- Integer Programming Methods -- Nonlinear Programming Models -- Nonlinear Programming Methods -- Models for Stochastic Processes -- Discrete-Time Markov Chains -- Mathematics of Discrete-Time Markov Chains -- Continuous-Time Markov Chains -- Mathematics of Continuous-Time Markov Chains -- Queuing Models -- Queuing Networks and Decision Models -- Simulation.
Includes bibliographical references and index.
One CD-ROM in pocket attached to inside front cover.
1
Keywords: Operations research; Operations research -- Mathematical models; Programming (Mathematics)